Effectiveness and Tolerability of Rufinamide in Children and Young People: A Survey of Experience from the United Kingdom - Tan, Hui Jeen; Awadh, Mostafa; O'Regan, Mary; Martland, Timothy R.; Kneen, Rachel (Journal of Pediatric Epilepsy, 2017)
The purpose of this study was to collate information on the clinical use of rufinamide in a pediatric population with epilepsy. A standardized proforma was sent to a group of pediatric neurologists and pediatricians in the United Kingdom requesting information about patients who were prescribed rufinamide. A total of 76 patients, with a median (range) age of 10.2 (2.8–19.8) years, were included. The patients had heterogeneous epilepsy syndromes, including 30 (39.5%) with Lennox-Gastaut syndrome (LGS), refractory to a minimum of three previous antiepileptic drugs. The median (range) maintenance dose of rufinamide was 25.4 (6.3–60) mg/kg/d. After 3 months of treatment, two (2.6%) of the 76 patients became seizure free, and 21 (27.6%) had ≥ 50% reduction in seizure frequency. The median (range) duration of treatment was 4.2 (0.5–38.4) months. At the last follow-up, 15 (19.7%) of the 76 patients continued with ≥ 50% reduction in seizure frequency; 2 of whom remained seizure free. Eighteen (23.7%) patients had treatment-emergent unwanted effects contributing to its discontinuation in nine (11.8%). In this study of a heterogeneous group of children and young people with medically refractory epilepsy on rufinamide, there was ≥ 50% seizure reduction in 30% at 3 months and 20% at the last follow-up.
Keywords: rufinamide; children; epilepsy